Peningkatan Literasi Pembayaran Non-Tunai di Pasar Badung Melalui Edukasi dan Sosialisasi QRIS - Surya Dharma Kumara, Anak Agung Bagus; Kalfika Anggria Wardani, Kadek Devi (J-Dinamika : Jurnal Pengabdian Masyarakat, 2023)
Pasar Badung as a traditional trading center has great potential to adopt a non-cash payment system to increase transaction efficiency and convenience. Pasar Badung is also known as the economic heart of Bali Province. This service activity aims to increase consumer literacy and understanding of digital payments in the form of QRIS. This activity was assisted by an informative poster entitled "Ngiring Ngangge QRIS" as an information medium. The results of this service show a significant increase in literacy in non-cash payments at the Badung Market. There was an increase in understanding of visitors after participating in this outreach. QRIS education and outreach are effective in increasing literacy in non-cash payments at the Badung Market. These steps encourage the adoption of modern payment technologies among visitors, contribute to transaction efficiency and increase awareness of the benefits of these technologies. It is hoped that the results of this service can become a reference for similar efforts to increase financial literacy in traditional markets and other sectors.